IMPLEMENTASI MANAJEMEN MUTU TERPADU DI SEKOLAH/MADRASAH - SAPUTRO, ANIP DWI (Universitas Islam Negeri Raden Intan Lampung, 2015)
School/Madrasah is the system of education in this country, school/Madrasah has a system of education, such as basic education, objectives, curriculum, methods, patterns student teacher relationship, and so forth. Such a system can be created using an integrated quality management through concepts, strategies and applications. That's all it took the setup process management to achieve educational goals effectively and efisien.Sistem effective and efficient could be in the form of the integrated quality management (MMT). Implementation of Integrated Quality Management in Schools/Madrasah wear integrated quality management (MMT). From the description it can be concluded that the management could dikatan as a process in order to achieve the goal by working together through people and other organizational resources. Management becomes a reference system for mengordinir and control all of the potential that exists within a particular organization. The aim is to arrange everything so well done, accurate and complete. With reference to the quality standards of Government Regulation No. 19 Year 2005 on National Education Standards, which includes the provision of the eight standards, namely: 1) Standard Competency, 2) Content Standards, 3) Processing Standards, 4) Standards of Education and the Workforce, 5) Infrastructure Standards, 6) Standard Management, 7) Financing Standards Education, 8) Education Assessment Standards. Implementation of Integrated Quality Management Schools/Madrasah there are several strategies that can be implemented by the school/madrasah among others, include a self-evaluation to analyze the strengths and weaknesses of the school/madrasah. Based on the evaluation of school madrasah together parents and society determines the vision and mission of the school/madrasah in improving the quality of education or formulate the expected quality and continued with planning school programs/madrasah including financing, with reference to priorities and national policies in accordance with the conditions of the school/madrasah and resources available. Keywords: quality management and the school